Examiners' psychological factors as correlates of absenteeism and attitude towards west African school certificate examination (WASSCE) assessment (2010)
It is important that all public examinations should be assessed highly accurately. In Nigeria and internationally across Anglophone West Africa, examinations for the West African Senior School Certificate (WASSC) influence the fututres of millions of candidates. In this study, the purpose was to determine examiners' psychologival factors as correlates of thier absenteeism and attitude towards WASSCE assessment. The variables that were hypothesized include the examiner's status/rank, assessment experience and age. An examiner questionnaire was constructed with a reliability coefficeient of 0.82, using Cronbach's alpha. The instrument was administered to one thousand and sixty-eight (1068) examiners selected through simple random and purposive sampling techniques across 70 assessment venues. Cross tabultion, X2 and simple regression analysis were used to determine the examiners psychological factors as correlates of absenteeism and attitude towards WASSCE assessment. Our findings seems useful where evidence based decisions surrounding examiners recruitments are needed in public assessment, particularly for the WASSCE assessment procedures.